Strategi Bisnis Yang Berorientasi Konsumen - Dasipah, Euis (Jurnal Social Economic of Agriculture, 2018)
Use of philosophy The concept in a company program is the business that is in the organization, not only those who are responsible for the sales department and also. Organizational development requirements to differentiate between users for several activities used to manage resources and performance required by project management, allow to develop and improve performance, create programs and develop strong programs, creating the fundamental performance. the market, develop a commitment to consumers throughout the organization.Keywords: business strategy, consumer